2016
DOI: 10.20471/acc.2016.55.02.07
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Anthropometry in Acute St-Elevation Myocardial Infarction Treated With Primary Percutaneous Coronary Intervention

Abstract: SUMMARY -Th e aim of this study was to investigate the controversial infl uence of anthropometry on clinical severity and prognosis of acute ST-elevation myocardial infarction (STEMI). We prospectively analyzed 250 patients with acute STEMI treated with primary percutaneous coronary intervention (September 2011 -September 2012. Th ey were grouped according to the following anthropometric parameters: body mass index (BMI) (<25.0, 25.0-29.9, ≥30.0 kg/m²), waist circumference (WC) (<102/88, ≥102/88 cm), waist-to-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 17 publications
(18 reference statements)
0
12
0
Order By: Relevance
“…Using multivariable logistic regression models, Son et al [24] also found significant relationships between WC and enlargement of LA and LV and LV hypertrophy in healthy male Koreans. Mornar Jelavić et al [16] reported that among patients with acute ST-elevation myocardial infarction (STEMI) treated with the percutaneous coronary intervention (PCI), those with abdominal adiposity defined by greater WHR values had higher rates of significantly stenosed proximal/middle coronary segments, while those with a greater WHtR had the highest rates of heart failure and total in-hospital complications. Markus et al [7] used multivariable-adjusted linear regression models to analyze the effect of changes in body composition measured using BIA during a 5 year period on changes in LV geometry and function.…”
Section: Discussionmentioning
confidence: 99%
“…Using multivariable logistic regression models, Son et al [24] also found significant relationships between WC and enlargement of LA and LV and LV hypertrophy in healthy male Koreans. Mornar Jelavić et al [16] reported that among patients with acute ST-elevation myocardial infarction (STEMI) treated with the percutaneous coronary intervention (PCI), those with abdominal adiposity defined by greater WHR values had higher rates of significantly stenosed proximal/middle coronary segments, while those with a greater WHtR had the highest rates of heart failure and total in-hospital complications. Markus et al [7] used multivariable-adjusted linear regression models to analyze the effect of changes in body composition measured using BIA during a 5 year period on changes in LV geometry and function.…”
Section: Discussionmentioning
confidence: 99%
“…However, there was no agreement in the literature 12 14 with regards to the best obesity parameter for predicting CAD (either stenosis or percentage) or its related symptoms. It has been evidenced in the literature that central obesity is a leading cause of the development of CAD or its related symptoms 20 22 .…”
Section: Discussionmentioning
confidence: 93%
“…They also explained that physicians may suspect CAD among obese patients earlier than among non-obese patients and may therefore pay closer attention to obese patients with regards to the development of CAD or its related symptoms. www.nature.com/scientificreports/ However, there was no agreement in the literature [12][13][14] with regards to the best obesity parameter for predicting CAD (either stenosis or percentage) or its related symptoms. It has been evidenced in the literature that central obesity is a leading cause of the development of CAD or its related symptoms [20][21][22] .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Our finding of a difference in intermediate chronotype and diabetes mellitus type 2 in female patients is important because of the influence of metabolic syndromes on circadian rhythm and CVD. Diabetes type 2 increases the risk of CVD ( 13 , 30 ). Metabolic syndromes, diabetes mellitus type 2, dyslipidemia, and smoking were not associated with ESS score in our study and the study by Whitney et al ( 31 ), whereas other studies found an association ( 15 , 32 ).…”
Section: Discussionmentioning
confidence: 99%